Pengaruh Jangka Pendek dan Jangka Panjang Impor Indonesia terhadap Stabilitas Nilai Tukar Rupiah Tahun 2010-2022 - Putri Mellynia; Tiara Nirmala; Nurbetty Herlina Sitorus; Thomas Adrian (Departement of Mathematics Education, 2024)
This research aims to determine the effect of imports on the rupiah exchange rate in the short and long term. The method used in this research is Vector Error Correction (VECM) using time series data. The dependent variable in this research is the rupiah exchange rate (ER) and the independent variable is imports (IM). The results of this research show that imports have a positive and significant influence in the short term and also have a significant positive influence in the long term on the rupiah exchange rate.